Using research to influence public policy : what works and how - Eboh, Eric C. (Enugu, Nigeria : African Institute for Applied Economics, 2014)
A blending of theoretical postulations and practical exoerience to unravel what is often refrred to as the "black box" between policy research and policy making. It elucidates what works and how.
Includes bibliographical references.
oif 15/06/15
Loan
Keywords: Policy sciences; Public policy; Policy research